Differential expression of VGLUT3 in laboratory mouse strains: Impact on drug‐induced hyperlocomotion and anxiety‐related behaviors. (6th November 2018) - Sakae, Diana Y.; Ramet, Lauriane; Henrion, Annabelle; Poirel, Odile; Jamain, Stéphane; El Mestikawy, Salah; Daumas, Stéphanie
Abstract : The atypical vesicular glutamate transporter VGLUT3 is present in subpopulations of GABAergic interneurons in the cortex and the hippocampus, in subgroups of serotoninergic neurons in raphe nuclei, and in cholinergic interneurons in the striatum. C56BL/6N mice that no longer express VGLUT3 (VGLUT3 −/− ) display anxiety‐associated phenotype, increased spontaneous and cocaine‐induced locomotor activity and decreased haloperidol‐induced catalepsy. Inbred mouse strains differ markedly in their sensitivity to anxiety and behavioral responses elicited by drugs. The purpose of this study was to investigate strain differences in VGLUT3 expression levels and its potential correlates with anxiety and reward‐guided behaviors. Five inbred mouse lines were chosen according to their contrasted anxiety and drugs sensitivity: C57BL/6N, C3H/HeN, DBA/2J, 129/Sv, and BALB/c. VGLUT3 protein expression was measured in different brain areas involved in reward or mood regulation (such as the striatum, the hippocampus, and raphe nuclei) and genetic variations in Slc17a8, the gene encoding for VGLUT3, have been explored. These five inbred mouse strains express very different levels of VGLUT3, which cannot be attributed to the genetic variation of the Slc17a8 locus. Furthermore, mice behavior in the open field, elevated plus maze, spontaneous‐ and cocaine‐induced locomotor was highly heterogeneous and only partially correlated to VGLUT3 levels. These data highlight the fact that one single gene polymorphism could not account for VGLUT3 expression variations, and that region specific VGLUT3 expression level variations might play a key role in the modulation of discrete behaviors. Abstract : Laboratory mouse lines express highly different VGLUT3 protein levels in the brain, partially explained by genetic variation.